Economic growth and development with low‐carbon energy. (9th October 2017) - Fankhauser, Sam; Jotzo, Frank
Abstract : Energy is needed for economic growth, and access to cheap, reliable energy is an essential development objective. Historically most incremental energy demand has been met through fossil fuels; however, in future that energy will have to be low carbon and ultimately zero‐carbon. Decarbonization can and needs to happen at varying speeds in all countries, depending on national circumstances. This article reviews the implications of a transition to low‐carbon energy on economic growth and development in current low‐income countries. It sets out empirical findings about trajectories for energy intensity and emissions intensity of economic growth; explores pathways to accelerate decarbonization; reviews the theoretical and empirical literature on economic costs and co‐benefits of energy decarbonization; and assesses analytical approaches. It discusses the opportunities that might arise in terms of a cleaner, more dynamic and more sustainable growth model, and the options for developing countries to implement a less‐carbon intensive model of economic development. WIREs Clim Change 2018, 9:e495. doi: 10.1002/wcc.495 This article is categorized under: Climate Economics > Economics and Climate Change Climate and Development > Decoupling Emissions from Development Abstract : Historically most incremental energy demand has been met through fossil fuels; however, in future that energy will have to be low carbon and ultimately zero carbon. Decarbonization can and needs to happen at varying speeds in all countries, depending on national circumstances.